2021
DOI: 10.1038/s41598-021-85008-9
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic prospecting for cryptic species of the genus Merluccius (Actinopterygii: Merlucciidae)

Abstract: Hakes of the genus Merluccius include 11 valid species as well a number of rare morphotypes suspected to be “cryptic species”. Concatenated nucDNA ITS1-rDNA and mtDNA cyt b sequences plus nested ITS1Nes sequences allowed to ascribe 14 specimens of nine rare morphotypes from the South Pacific and the South Atlantic to the phylogenetic backbone of this genus. Bayesian analyses pointed to M. bilinearis and M. albidus as the oldest species of the genus and the New World cluster, respectively. The phylogenetic stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…Generated COI and 16S rRNA sequences were deposited in GenBank (Accession numbers: COI, MZ540345-MZ540346; 16S rRNA, MZ540342-MZ540344). The maximum likelihood tree generated with COI and 16S rRNA revealed a clear separation of M. merluccius from other Merluccius species, in harmony with previous reports (Campo et al, 2007;Perez et al, 2021;Quinteiro et al, 2000). The Black Sea specimens nested with reference M. merluccius sequences, yet there was no clear separation based on geographic origin (Figure 2).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Generated COI and 16S rRNA sequences were deposited in GenBank (Accession numbers: COI, MZ540345-MZ540346; 16S rRNA, MZ540342-MZ540344). The maximum likelihood tree generated with COI and 16S rRNA revealed a clear separation of M. merluccius from other Merluccius species, in harmony with previous reports (Campo et al, 2007;Perez et al, 2021;Quinteiro et al, 2000). The Black Sea specimens nested with reference M. merluccius sequences, yet there was no clear separation based on geographic origin (Figure 2).…”
Section: Resultssupporting
confidence: 88%
“…The genus Merluccius comprises 12 species widely distributed along the coasts of Europe, America, and Africa. Phylogenetic analysis based on mitochondrial and nuclear sequences indicates the presence of two distinct clades: American clade and Euro-African clade (Campo et al, 2007;Perez et al, 2021;Quinteiro et al, 2000). The Euro-African clade includes the European hake.…”
Section: Introductionmentioning
confidence: 99%
“…It is plausible that these winter samples included Pacific Hake that typically resided farther south in the range but had migrated farther north due to warmwater conditions, although this is speculative. To better assess this possibility, genomic analyses of Pacific Hake off the coast of Mexico and further south are warranted, as previous genetic work found equivocal levels of differentiation in these regions (Silva-Segundo et al 2011;Iwamoto et al 2015;García-De Leon et al 2018;Pérez et al 2021). Additionally, our outlier analyses detected 29 loci putatively under selection when including SS samples and suggested that adaptive differences have evolved in the inland resident populations.…”
Section: Discussionmentioning
confidence: 80%
“…2018; Pérez et al. 2021). Previous genetic work in Pacific Hake identified three genetically distinct populations: a coastal population from Queen Charlotte Sound to Costa Rica (from 55°N to 10°N); a resident population in the inland waters of the Salish Sea (SS), which is characterized by weak differentiation among regions (i.e., Puget Sound and the Strait of Georgia [SOG]); and a third population isolated in the northern Gulf of California (Iwamoto et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation